Flexural Strengthening of RC Slabs Using a Hybrid FRP-UHPC System Including Shear Connector - Jiho Moon; Mahmoud M. Reda Taha; Jung J. Kim (Advances in Materials Science and Engineering)
A polymeric hybrid composite system made of UHPC and CFRP was proposed as a retrofit system to enhance flexural strength and ductility of RC slabs. While the effectiveness of the proposed system was confirmed previously through testing three full-scale one-way slabs having two continuous spans, the slabs retrofitted with the hybrid system failed in shear. This sudden shear failure would stem from the excessive enhancement of the flexural strength over the shear strength. In this study, shear connectors were installed between the hybrid system and a RC slab. Using simple beam, only positive moment section was examined. Two full-scale RC slabs were cast and tested to failure: the first as a control and the second using this new strengthening technique. The proposed strengthening system increased the ultimate load carrying capacity of the slab by 70%, the stiffness by 60%, and toughness by 128%. The efficiency of shear connectors on ductile behavior of the retrofitted slab was also confirmed. After the UHPC top is separated from the slab, the shear connector transfer shear load and the slab system were in force equilibrium by compression in UHPC and tension in CFRP.